2018
DOI: 10.1136/bmj.k3702
|View full text |Cite
|
Sign up to set email alerts
|

What should doctors say to men asking for a PSA test?

Abstract: Patients need individual discussions about the benefits and harms of testing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Nonetheless, Figure 4 indicates that these sampling methods increase the AUC, suggesting we should hold onto them. This is in line with what you would expect from an imbalance correction method, but it does reflect that further optimization needs to be done, especially as false positives are currently a problem with PSA tests [5]. predictor performed the best in terms of every metric shared between all the predictors aside from specificity, with its specificity being 0.0095 less than that of our PoHRPC predictor.…”
Section: Comparison Of the Results With Related Worksupporting
confidence: 77%
See 2 more Smart Citations
“…Nonetheless, Figure 4 indicates that these sampling methods increase the AUC, suggesting we should hold onto them. This is in line with what you would expect from an imbalance correction method, but it does reflect that further optimization needs to be done, especially as false positives are currently a problem with PSA tests [5]. predictor performed the best in terms of every metric shared between all the predictors aside from specificity, with its specificity being 0.0095 less than that of our PoHRPC predictor.…”
Section: Comparison Of the Results With Related Worksupporting
confidence: 77%
“…One very common screening method is the measurement of prostate-specific antigen (PSA), which is a protein produced by cells of the prostate gland. However, it has been shown that monitoring PSA levels has no significant impact on prostate cancer mortality after a median follow-up of 10 years with those who had this monitoring [4,5]. The United States Preventative Services Task Force (USPSTF) originally issued a recommendation against PSA screening for all ages in 2012 [6], but in 2017 revised that recommendation to say that the decision to undergo PSA testing is an individual decision for men between 55 and 69 years of age, with those over 70 still being recommended against PSA screening [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Over half of UK hospitals now use multiparametric-MRI to protect men from the harms of unnecessary biopsy and treatment for indolent prostate cancer. 4 The important question Just and colleagues raise is not which test should be performed once a patient is referred for suspected prostate cancer, but rather should patients with non-specific symptoms be tested in primary care and are there harms of testing them?…”
mentioning
confidence: 99%
“…Primary care clinicians are generally aware of the limitations of PSA testing (39), and clinical guidelines encourage a balanced discussion with patients of the potential bene ts and harms of relying on PSA to detect prostate cancer (40,41). The ndings of this review suggest this is a pragmatic approach in providing care to patients with LUTS.…”
Section: Implications For Research and Practicementioning
confidence: 99%